PERANAN STRATEGI PENETAPAN HARGA UNTUK MENINGKATKAN PENJUALAN RITEL - CHANDRA, FENITA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Pricing decisions are increasingly important as current customers tend to look for the value (value) when buying goods or services. In the retail market, there are now two different pricing strategies, namely: (1) low daily pricing (everyday low pricing-EDLP) that emphasizes the continuity of the retail price on the level between regular and sale prices of non sale price discounting retail competitor (not necessarily the cheapest) and (2) the determination of the price high or low (high/low pricing-HLP), where retail prices are sometimes above the EDLP of competitors, using advertising to promote the sale of high-frequency EDLP pricing strategies or pricing strategies HLP, both can be used by retailers to increase their sales. If the retailer aims to decrease price wars, reduced advertising, reduced excess inventory, then retailers must uses the EDLP strategy. Conversely, if the retailer aims to lure a wide market, creating the excitement of shopping cart (with a clearance sale), increasing the volume sales of the product group that is not sold, then selling retailers use HLP strategy..